Evaluation of in vitro gas production of roughages and their mixtures using the curves subtraction method - Campos, F. P.; Sampaio, AAM; Bose, MLV; Vieira, R. F.; Sarmento, P. (Elsevier B.V., 2004)
The in vitro gas production of four single roughages and their paired combinations (1:1 on dry matter basis) were evaluated. Two roughage samples (100 mg) per treatment were fermented with ruminal fluid during a 48 h incubation period. Total 48 h gas volumes of fermentation dry matter (DM), neutral detergent fiber (NDF) and soluble compounds in neutral detergent (NDS) were for sugarcane = 16.8, 11.2, 6.9 mL; sugarcane + corn silage = 20.1, 12.6, 9.1 mL; sugarcane + 60-day elephantgrass = 16.5, 17.6 mL; sugarcane + 180-day elephantgrass = 13.8, 8.2, 5.9 mL; corn silage = 18.8, 16.8, 4.7 mL; corn silage + 60-day elephantgrass = 16.3, 15.4, 2.4 mL; corn silage + 180-day elephantgrass = 16.1, 11.8, 4.2 mL; 60-day elephantgrass = 16.9, 19.0 mL and 180-day elephantgrass = fermented 10.7, 12.2 mL, respectively. The NDS gas production was not possible to estimate for sugarcane + 60-day elephantgrass, 60-day elephantgrass and 180-day elephantgrass. The present data shows that the curves subtraction method can be an option to evaluate the contribution of the soluble fractions in roughages to digestion kinetics. However, this method underestimates the NDS gas contribution when roughages are low in crude protein and soluble carbohydrates. It is advisable to directly apply the two-compartmental mathematical model to the digestion curves for roughage DM, when determining the NDS gas volume and the digestion rate. This method is more straightforward and accurate when compared to the curve subtraction method. Non-structural carbohydrates combined with fiber and protein promoted a positive associative effect in sugarcane + corn silage (50:50) mixture. Therefore, it can be concluded that the soluble fraction of roughages greatly contributes to gas production. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: corn silage; elephantgrass; roughages; soluble carbohydrate; Sugarcane